Mechanistic insights into the protective role of eugenol against stress-induced reproductive dysfunction in female rat model - Helmy, Hebatullah; Hamid Sadik, Nermin Abdel; Badawy, Laila; Sayed, Noha H. (Chemico-biological interactions, 2022)
The challenging and highly demanding life rhythm nowadays subjects people to unavoidable chronic stress. Chronic stress is associated with a wide array of serious health complications including neuroendocrine dysregulations. Women are more prone to chronic stress-related hormonal disturbances and their physical and psychological consequences, especially reproductive impairment. Eugenol is a natural phenolic anti-oxidant that has several beneficial biological activities. The current study intended to scrutinize the potential protective effect of eugenol in female Wistar rats exposed to chronic unpredictable mild stress (CUMS). Rats were randomly allocated into 4 groups; group 1 received olive oil, group 2 received eugenol in olive oil, groups 3 and 4 were subjected to CUMS protocol for 8 weeks, with pre- and concomitant treatment with eugenol (50 mg/kg/day; p.o.) in group 4. The results showed that CUMS exposure led to weight loss and depressive-like behaviours. CUMS induced hypothalamic-pituitary-adrenal axis activation with subsequent elevation of serum corticosterone level which, in turn, caused decline in ovarian release of estradiol and antimullerian hormones together with an increased production of follicle-stimulating and luteinizing hormones by the anterior pituitary, leading to reproductive disturbances. In ovaries, CUMS imposed oxidative stress, insulin resistance and molecular damage. Intriguingly, all these adverse effects were significantly mitigated by the administration of eugenol that improved animals’ behaviours, corrected corticosterone upsurge, tempered hormonal disturbances, and amended ovarian damage. All biochemical results were further confirmed by hippocampal and ovarian histopathological examinations. In conclusion, the current study highlights the prophylactic role of eugenol against reproductive disturbances induced by chronic stress in female rats. [Display omitted] •Chronic stress triggers reproductive disturbances in females.•Eugenol intake protects against reproductive dysfunction induced by chronic stress.•Eugenol controls stress-induced hyper activated hypothalamic-pituitary-adrenal axis.•Eugenol reduces oxidative stress and restores insulin sensitivity in ovarian stress-insulted tissues.